Effects of Covering Surgical Wounds with Polyglycolic Acid Sheets for Posttonsillectomy Pain. (November 2016) - Miyaguchi, Shin-ichi; Horii, Arata; Kambara, Rumi; Takemoto, Norihiko; Akazawa, Hitoshi; Takahashi, Nao; Baba, Hironori; Inohara, Hidenori
Postoperative pain is a remaining issue in tonsillectomy. Polyglycolic acid (PGA) is a biocompatible material used for absorbent suture reinforcement, and its sheet has been applied for covering defects after resection of oral carcinoma. The aim of this study is to examine whether the attachment of a PGA sheet to surgical wounds would reduce posttonsillectomy pain. In this prospective single-blind study, 17 consecutive adult patients were recruited who needed to undergo tonsillectomy, mainly due to habitual tonsillitis. Following bilateral tonsillectomies, a PGA sheet was attached with fibrin glue to only 1 side, without notification to patients of which side. Postoperative pain of each side was separately evaluated with a visual analog scale at 4 time points: before each meal and before sleep. Postoperative pain of both the PGA sheet–attached and nonattached sides was most severe before breakfast among 4 time points. Postoperative pain measured before breakfast was significantly more severe in the PGA sheet–attached side than the nonattached side. As such, this study provided solid data on the negative effects of PGA sheeting on posttonsillectomy pain.